2018
DOI: 10.3390/ijms19061700
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte Motility Is Affected by UVA Radiation—A Comparison between Normal and Dysplastic Cells

Abstract: UVA radiation induces multiple and complex changes in the skin, affecting epidermal cell behavior. This study reports the effects of UVA exposure on normal (HaCaT) and dysplastic (DOK) keratinocytes. The adherence, spreading and proliferation were investigated by time-lapse measurement of cell layer impedance on different matrix proteins. Prior to UVA exposure, the time required for adherence and spreading did not differ significantly for HaCaT and DOK cells, while spreading areas were larger for HaCaT cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…UVA exposure was reported to affect these cell populations differently in terms of migration and proliferation. It was previously demonstrated that dysplastic cells are less able to spread across a denuded area than normal keratinocytes, and were more affected than the latter by UVA treatment [ 17 ]. In terms of cell proliferation, UVA exposure induced cell-cycle arrest for normal keratinocytes [ 20 , 21 ]; this outcome, reviewed in [ 22 ], may lead to an increased doubling time of a cell population, a finding which also was observed in our real-time, impedance-reading experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…UVA exposure was reported to affect these cell populations differently in terms of migration and proliferation. It was previously demonstrated that dysplastic cells are less able to spread across a denuded area than normal keratinocytes, and were more affected than the latter by UVA treatment [ 17 ]. In terms of cell proliferation, UVA exposure induced cell-cycle arrest for normal keratinocytes [ 20 , 21 ]; this outcome, reviewed in [ 22 ], may lead to an increased doubling time of a cell population, a finding which also was observed in our real-time, impedance-reading experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Further dilutions were made with complete cell culture medium and appropriate controls containing a comparable dilution of DMSO. Cells were exposed to UVA with a UV-365 nm lamp (VL-340 BLB model—Vilber Lourmat, France) at a light intensity of 381 µW/cm 2 , for 30 min, in a laminar flow hood, as previously described [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the molecular mechanisms of cell motion and cellular proliferative capacity need to be investigated. 4143…”
Section: Discussionmentioning
confidence: 99%
“… Typical round-shaped images of the keratinocytes cytoskeleton (arrows) obtained by immunofluorescence, from Niculiţe et al [ 26 ]. Copyright MDPI, 2018 ( a ).…”
Section: Figurementioning
confidence: 99%